An assessment on the condition of English among construction undergraduates - Khairuddin, Sufi Solheya; Abdul Rashid, Khairuddin (2008)
This paper reports on a preliminary study to assess the condition of written English among construction undergraduates. The study, using the content analysis method, examined written works belonging to first year construction undergraduates (cohort 2006107) in identifying and analysing errors in spelling, grammar and syntax. The key findings of the study are that the problems of spelling and grammatical errors are not serious, but syntax error is most widespread and is considered serious. The findings provided evident to support the notion that the standard of English among construction undergraduates is relatively poor.